THE INFLUENCE OF THE RECRUITMENT AND SELECTION PROCESS ON EMPLOYEE PERFORMANCE AT PT. PADMA SOODE INDONESIA - Terris Febri Andika; Ari Sulistyowati; Christoporus Indra Wahyu; Tyna Yunita (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This study aims to see the extent of the influence of the independent variable of the Recruitment Process and the free variable of Selection on the variable tied to Employee Performance partially or simultaneously. This research was conducted at PT Padma Soode Indonesia located on Jl. Raya Narogong No.KM.15 Ciketing Udik, Bantar Gebang District, Bekasi City, West Java. The type of research used in this study is a quantitative approach. The sample in this study used the Random Sampling technique. The data obtained is primary data from the results of questionnaire answers distributed to 92 respondents and processed using the SPSS program version 22. The results showed that in the partial t test, the Recruitment Process variable did not have a significant effect on Employee Performance and the Selection Variable had a significant effect on Employee Performance. In Test F, the variables of the Recruitment and Selection Process simultaneously affect Employee Performance. The next suggestion to researchers is to conduct research by adding other variables such as placement and with a larger number of respondents